Unusual presentation of Wilms' tumor as umbilical granuloma - Shalini Gajanan Hegde; Prema Menon; Katragadda Lakshmi Narasimha Rao; Ritambhra Nada (Indian Journal of Medical and Paediatric Oncology)
We report an unusual presentation of a Wilms' tumor in an 8-month-old child, incidentally detected by ultrasonography for an umbilical granuloma. A patent vitellointestinal duct anomaly required surgical excision in the same sitting as the nephroureterectomy. The case is reported for the unusual coexistence and the management implications.